Role of rhubarb and α-keto analogues of essential amino acids supplementation in halting progression of chronic kidney disease - Khan, Irfan Ahmad; Nasiruddin, Mohammad; Haque, Shahzad F.; Khan, Rahat A. (International Journal of Research in Medical Sciences, 2017)
Background: Chronic kidney disease (CKD) is an emerging chronic disease due to rapidly increasing incidence of diabetes and hypertension worldwide. Newer drugs are being searched which can stop nephron damage and are cost effective. This study was undertaken to compare the efficacy and safety profile of rhubarb and α-keto analogues of essential amino acids supplementation in patients of chronic kidney disease. Methods: A prospective comparative study was conducted in patients of chronic kidney disease attending Renal Clinic of a tertiary care centre. Randomization of patients was done into three interventional groups: conservative management along with placebo was given in first group (Control); conservative management along with Rhubarb capsule (350 mg, thrice daily) was given in second group (Rhubarb) and conservative management along with α-keto analogues of essential amino acids (600 mg, thrice daily) was given in third group (KAA). The treatment was given for 12 weeks. Clinical and biochemical parameters were assessed at 0, 4, 8 and 12 weeks of treatment. Results: Patients of all three groups showed gradual improvement in clinical features and biochemical parameters as compared to their pre-treated values which was more marked in KAA supplemented group. There was reduction in: fasting blood glucose (12.51%, 19.15% and 20.78%), PPBG (14.80%, 19.00% and 20.89%), serum creatinine (25.00%, 30.54% and 39.52%), blood urea (25.55%, 33.64% and 38.09%), and 24-hour total urine protein (TUP) (19.80%, 30.18% and 38.34%) in Group I, II and III respectively. There was increase in: haemoglobin level (12.64%, 14.99% and 19.77%), 24-hour total urine volume (TUV) (19.41%, 28.82% and 33.32%) and GFR (22.6%, 46.5% and 49.2%) in Group I, II and III respectively. Rhubarb and KAA supplementations were safe and well-tolerated. Conclusions: KAA is more effective than Rhubarb as add on therapy with conservative management in patients of chronic kidney disease.